2018
DOI: 10.4028/www.scientific.net/jbbbe.38.38
|View full text |Cite
|
Sign up to set email alerts
|

Silicocarnotite Synthesis and Bioactivity in Artificial Saliva Medium

Abstract: The aim of this study is the synthesis and investigation of bioactive response of acrystalline silicophosphate.A monophasic silicocarnotite was elaborated by solid state reaction from a mixture of beta-tricaliciumphosphate and dicalcium silicate based on mussel shells according to the diagram of system Ca3(PO4)2–Ca2SiO4, at 65 % and 35% respectively , these starting materials are heated up to 1450 °C to obtain a monophasic silicocaronitite. The obtained result probed that the main crystalline phase which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, highly promising studies with silicon-substituted calcium phosphates have shown that silicon is an essential trace element for bone mineralization and can improve the bioactivity of calcium phosphate materials [36][37][38][39][40][41]. The wide range of CaO, SiO 2 , and P 2 O 5 solid solutions varies with temperature and makes silicocarnotite (Ca 5 (PO 4 ) 2 SiO 4 ) [32,34,[42][43][44][45] an excellent ceramic with great potential for medical applications [41,[45][46][47][48], which creates interest in knowledge about its synthesis conditions [35,46,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly promising studies with silicon-substituted calcium phosphates have shown that silicon is an essential trace element for bone mineralization and can improve the bioactivity of calcium phosphate materials [36][37][38][39][40][41]. The wide range of CaO, SiO 2 , and P 2 O 5 solid solutions varies with temperature and makes silicocarnotite (Ca 5 (PO 4 ) 2 SiO 4 ) [32,34,[42][43][44][45] an excellent ceramic with great potential for medical applications [41,[45][46][47][48], which creates interest in knowledge about its synthesis conditions [35,46,49,50].…”
Section: Introductionmentioning
confidence: 99%